Pesticides use and toxicity: survey in the agricultural zone of San Vicente, Santa Fe, Argentina - Alberto Schaaf, Angel Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
The consumption of pesticides in Argentina has been consolidated along with agricultural expansion in recent years. This consolidation has set such products as one of the fundamental pillars of production growth in view of the expected development over the medium term. Pesticide exposure can affect health and environment in various ways. The aim of this work was to make a list of the main pesticides used in land spraying in the agricultural area of San Vicente, Santa Fe, from 2009 to 2011, in order to classify them according to their toxicological category and its toxicity in birds, bees and fish. For this we conducted a survey of the types of pesticides in the agricultural zone. The results obtained indicate that the most toxic pesticides are among the group of insecticides. It is extremely necessary to monitor these products to ensure proper management of the agricultural area and an improved environmental quality.
Keywords: agrochemicals; crop; ecotoxicity; environmental